9 heads : a guide to drawing fashion - Riegelman, Nancy; 9 Heads Media ([Los Angeles, Calif.] : 9 Heads Media, 2012)
9 Heads' is a clear and comprehensive guide to the fundamentals of fashion drawing in black and white. It demonstrates that drawing can be learned by the application of a set of rules and guidelines, together with commitment and practice.
Previous ed.: 2006.
Includes index.
Accompanying CD-ROM includes: video (MP-4) ; templates ; photoshop drawings ; jpeg, tiff, and silhouette files.
System requirements for accompanying CD-ROM: PC ; Quicktime ; Photoshop ; CD-ROM drive.
Keywords: Fashion drawing -- Technique